Мониторинг экономических процессов при коррелированных результатах наблюдений - Тимофеев, В. А.; Кирій, В. В. (ХНУРЭ, 2014)
The problem of monitoring of economical processes is considered. The solving of tasks of economical monitoring is connected with solving of the problems of the recognition, Identification and forecast. Proposed solving of the problems of economical monitoring using the procedures of the method of instrumental variables (MIV). The different modifications of the MIV are discussed in this paper.
Keywords: коррелированный результат; задачи мониторинга; линейное регрессионное уравнение; степень коррелированности; метод наименьших квадратов; метод инструментальных переменных